2022
DOI: 10.1002/anie.202207518
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Dearomative Cyclization Enabled by Asymmetric Cooperative Gold Catalysis

Abstract: A gold(I)‐catalyzed enantioselective dearomatization is achieved via metal‐chiral ligand cooperation. A new and divergent synthesis of chiral bifunctional binaphthyl‐2‐ylphosphines is developed to allow rapid access to these ligands, which in turn facilitate the application of this chemistry to a broad substrate scope including 1‐naphthols, 2‐naphthols, and phenols. Enantiomeric excesses up to 98 % are achieved via selective acceleration of one enantiomer formation enabled by hydrogen bonding between substrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 53 publications
1
29
0
Order By: Relevance
“…Recently, a gold(I)catalyzed enantioselective dearomatization of naphthol and phenol derivatives 111 was achieved by You and co-worker (Scheme 25c). [45] A new and divergent synthesis of chiral bifunctional binaphthyl-2-ylphosphines was developed to allow rapid access to spirocarbo-cycles 112. The products featured a spirocarbocyclic skeleton bearing a chiral all-carbon quaternary centre and a synthetically versatile enone functionality.…”
Section: Au-catalyzed Dearomative Vinylation Reactions Of Electron Ri...mentioning
confidence: 99%
“…Recently, a gold(I)catalyzed enantioselective dearomatization of naphthol and phenol derivatives 111 was achieved by You and co-worker (Scheme 25c). [45] A new and divergent synthesis of chiral bifunctional binaphthyl-2-ylphosphines was developed to allow rapid access to spirocarbo-cycles 112. The products featured a spirocarbocyclic skeleton bearing a chiral all-carbon quaternary centre and a synthetically versatile enone functionality.…”
Section: Au-catalyzed Dearomative Vinylation Reactions Of Electron Ri...mentioning
confidence: 99%
“…For a long period of time, enzymes 2,3 and metal complexes were the most commonly thought of examples of asymmetric catalysts. 4,5 With the development of green chemistry, natural chiral amino acids have gradually entered people's vision. It was found that the nitrogen-containing five-membered ring on the natural chiral amino acid structure has better catalytic effects for asymmetric reactions.…”
Section: Introductionmentioning
confidence: 99%
“…The catalytic alkyne cycloisomerization [2] represents a significant advance in the formation of molecular complexities developed by Toste, [3] Echavarren, [4] Hashmi, [5] Zhang, [6] Gagosz, [7] Zhu, [8] and others, [9] but these typical methodologies have so far been limited to activation by metal or Brønsted acid catalysts. Recently, explorations of alkyne cycloisomerization for the facile and practical construction of carbo-or heterocycles using molecular iodine have attracted considerable attention in organic synthesis, because I 2 is transition-metal-like active, low toxic, costeffective, commercially available, and easy to handle.…”
Section: Introductionmentioning
confidence: 99%